DEIKSIS PERSONA DALAM KONTEN INSTAGRAM SELEBGRAM BALI - Subur Made; Anak Agung Istri Manik Warmadewi; I Ketut Subagia (Universitas Warmadewa, 2024)
Instagram is one of the social media platforms that is currently being loved by the public. The development of Instagram has led to the emergence of the term celebgram which means Instagram celebrity. Celebrities usually have a large number of followers and consistently upload content in the form of photos and videos on their personal accounts. In communication on Instagram, the use of persona deixis is very important to create closeness and personalization. Two celebgrams from Bali, namely Gek Cantik and Gek Teplon, often upload their content in Balinese. In conveying messages in each content, they often use persona deixis. Persona deixis is a pronoun that is used to replace the thing or person being talked about. To find persona deixis in the content of Gek Cantik and Gek Teplon, qualitative descriptive methods were used in this research. There were 3 data found that used first person personal deixis and 3 data that used second person personal deixis. The use of third person persona deixis was not found in the analyzed content.